The Rule of Magnetic Resonance Angiography (MRA) in the Case of Angiofibroma in the Elbow Joint Region - Jauhari, Arif; Oktalita Perdani, Fathona (KnE Life Sciences, 2019)
Background: Using the MRI modality of 1.5 Tesla can alter vascular imaging (angiography) from invasive examination into a non-invasive examination. The Magnetic Resonance Angiography (MRA) can be performed on upper limb organs with and without contrast. One indication of the MRA examination is angiofibroma. Because of the pathology, clinicians want to see the flow of blood from the upper arm to the elbow so that body coil is used as an alternative to genu coil or ankle coil commonly used in this examination. Objective: The research intends to know how the technique of MRA elbow management using body coil in the angiofibroma case. Method: This research was conducted by observation. The researchers looked directly at the MRA elbow examination procedure using the body coil. Result: The result is the MRA elbow image using body coil from different sequences.